Cascade effects of seafloor litter on benthic ecosystems in the northern Yellow Sea - Teng, Guangliang; Shan, Xiujuan; Jin, Xianshi (Frontiers in Marine Science, 2023)
The accumulation of seafloor litter changes the habitats of benthic organisms and thus affects their spatial distribution. Previous studies suggested that the accumulation of seafloor litter might contribute to the bloom of Metridium senile fimbriatum, given that seafloor litter could serve as “vectors” for M. senile dispersal and provide with “natural habitat” for their settlement. As a common fouler and invader, M. senile bloom will inevitably affect the benthic ecosystem. The cascading effects of seafloor litter on benthic ecosystems can be explored by studying the interactions between this litter-associated anemone and other co-occurred species. Therefore, this study uses stable isotope analysis to study the food composition of M. senile attached to the seafloor litter and the niche relationship with co-occurred species. First, by comparing the stable isotope ratios of the pedal disc and tentacle of M. senile, it was found that the δ15N of the foot disc is more stable than that of the tentacle, so the pedal disc was chosen as the sampling tissue. The mean δ13C value of M. senile was -19.34 ± 0.86‰, which ranged from -22.30‰ to -18.17‰. For δ15N, the mean value was 12.02 ± 0.95‰, which ranged from 9.22‰ to 13.31‰. Then, we quantified the contribution of the potential food resources of M. senile using the SIMMR model. M. senile has the highest feeding proportion to crustaceans, followed by juvenile fish, zooplankton and other macrobenthos. Meanwhile, M. senile has high uncertainty in the feeding proportion of crustaceans and juvenile fish. In addition, the trophic niche overlap between different functional groups was calculated by the SIBER model, and the results showed that the isotopic niche of M. senile was overlapped with different functional groups, ranging from 34.29 to 35.25%. Therefore, this study suggests that M. senile, as litter-associated carnivorous anemone, interacts with other components in the ecosystem through predation and competition, which also reveals the cascade effect of seafloor litter on the benthic ecosystem of the northern Yellow Sea.